1995
DOI: 10.1097/00004032-199501000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Natural Effective Half-Life of 137Cs in Tea Plants

Abstract: Contamination levels and variation of 137Cs in tea plant leaves from 1986-1992 were determined over the coast line of the Eastern Black Sea region in Turkey. The decrease of 137Cs radionuclide concentration in tea plant leaves may be described by a double exponential function with 94.8% activity lost with a Teff of 125 d and 5.2% activity lost with a Teff of 1,114 d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…During the emergency, Cekmece Nuclear Research and Training Center performed an analysis of various substances. In their report, it was noted that the surface soil 137 Cs activity concentration of the eastern part of the Black Sea mountains was around 4-4.5 kBq kg À1 at the 0.5 cm soil in the year 1988 (Unlu et al, 1995). And also the level of 137 Cs activity concentration in Turkish tea plant was found to be the maximum value of 44 kBq kg À1 for the 1986 products by Gedikoglu and Sipahi (1989).…”
Section: Introductionmentioning
confidence: 94%
“…During the emergency, Cekmece Nuclear Research and Training Center performed an analysis of various substances. In their report, it was noted that the surface soil 137 Cs activity concentration of the eastern part of the Black Sea mountains was around 4-4.5 kBq kg À1 at the 0.5 cm soil in the year 1988 (Unlu et al, 1995). And also the level of 137 Cs activity concentration in Turkish tea plant was found to be the maximum value of 44 kBq kg À1 for the 1986 products by Gedikoglu and Sipahi (1989).…”
Section: Introductionmentioning
confidence: 94%
“…During the emergency, Cekmece Nuclear Research and Training Center (CANEM) performed an analysis of various substances. It their report, it has been noted that the surface soil 137 Cs activity concentration of the eastern part of the Black Sea mountains was around 4000-4500 Bq/kg at the 0.5cm soil in the year 1988 (7) .…”
mentioning
confidence: 95%
“…Among these radionuclides, 137 Cs with a half-life of w30 y has remained in the ecosystems many years after the accident. It was reported that the surface soil 137 Cs activity concentration of the Eastern Black Sea mountains was around 4-4.5 kBq kg À1 at the 0.5 cm soil in the year 1988 (Unlu et al, 1995). The level of 137 Cs activity concentrations in Turkish tea plants was found to be as high as 44 kBq kg À1 for the 1986 products (Gedikoglu and Sipahi, 1989).…”
Section: Introductionmentioning
confidence: 99%